Observations of Radio Magnetars with the Deep Space Network - Aaron B. Pearlman; Walid A. Majid; Thomas A. Prince (Advances in Astronomy)
The Deep Space Network (DSN) is a worldwide array of radio telescopes which supports NASA’s interplanetary spacecraft missions. When the DSN antennas are not communicating with spacecraft, they provide a valuable resource for performing observations of radio magnetars, searches for new pulsars at the Galactic Center, and additional pulsar-related studies. We describe the DSN’s capabilities for carrying out these types of observations. We also present results from observations of three radio magnetars, PSR J1745–2900, PSR J1622–4950, and XTE J1810–197, and the transitional magnetar candidate, PSR J1119–6127, using the DSN radio telescopes near Canberra, Australia.